Middle ear and mastoid surgery - Haberman, Rex S. (Thieme, 2004)
Describes the latest techniques for virtually every surgery performed in the middle ear and mastoid. It is organized not by anatomy or disease, but by operative procedure. Progressing from simple surgical techniques to more complicated procedures, the book covers: tympanoplasty; the various forms of mastoidectomy; initial and revision stapedectomy; ossiculoplasty; and much more. This easy-to-use book is sure to become the reference of choice for practicing otolaryngologists. It is also ideal for residents who need an easily accessible textbook of modern otological surgical techniques.